O poder dado por Cristo para expulsar o mal do meio dos homens: Uma Teologia do Ritual do exorcismo - Silva, Rafael Ferreira da (2018)
Objective: Approach in a theological way the Rite of Roman Exorcism. Allowing for greater dissemination of this important sacramental in the Church. Justification: There is more and more exposure on the subject of exorcism, whether in the media or in the assemblies of the faithful. However, this exhibition is full of folkloric, cultural and fanciful exaggerations. With this the need to scientifically approach the exorcism understood as a real combat that the Church assumes. Hypothesis: The Devil's action is real and he begins a battle with humanity that had already begun in the angelic field. Thus the Roman Rite of Exorcism exercises the mandate of Christ on the Apostolic Church, the power given by Christ to men to expel evil from the world. Methodology: Work divided into three chapters. In the first moment one seeks to know the evil nature of the devil, a fallen angel. As the development of the Holy Scriptures and Tradition recognizes the presence of the evil one and will show Jesus as the great exorcist. In the second chapter, the Church conscious of her ministry as an exorcist will develop the ritual over the centuries, from the apostolic age to the Second Vatican Council. In the third chapter an analysis of the Exorcism Ritual, observing its liturgical activity and how it is a true instrument of Spiritual Combat